Estudos estruturais e ensaios biológicos de proteínas codificadas por genes de micro-exon (MEG) de Schistosoma mansoni - Alves, Natália Oliveira (2014)
Schistosoma mansoni is the causative agent of Schistosomiasis, reaching 249 million people in 78 countries. It is believed that this infection is successful due to modulation of the host immune system through proteins secreted by the parasite. Recently a class of proteins derived from micro-exon genes (MEGs) was observed in proteomic analyses of schistosomula and egg secretions of S. mansoni, and also associated with glands of several stages of the parasite life. Furthermore, they found that none of these proteins showed similarity to proteins of organisms from other genres. In this context, aim of this work was the structural study, the search for protein partners and biological assays seeking possible roles for the proteins encoded by genes of micro-exons of S. mansoni: MEG-5, MEG-8.2 e MEG-12. For structural characterization studies we used MEG-5 protein expressed by heterologous system (the expression of MEG-8.2 protein was not obtained) and initially performed tests Circular Dichroism (CD). This essay revealed the predominance of one disordered structure due to the presence of a negative peak in the ranges of 180-200mm and the presence of lower intensity peaks in the range 220- 240mm, indicating that part of the protein may present structure. Such structure was observed in the secondary structure predictions performed in SOPMA and Jpred3 programs, wherein the presence of a predicted alpha-helix in the C-terminal region. To confirm this fact, we performed an analysis of the maximum emission of tryptophan fluorescence by the technique of intrinsic fluorescence, because the protein has a single tryptophan present in the probable alpha-helical region. We note that the maximum fluorescence emission is at 330mm, indicating that it is in more hydrophobic environment. After the structural characterization of MEG-5 protein we seek partners through the assay two-hybrid system performing a scan on leukocyte cDNA libraries, yielding two possible partners. The CHMP1B protein was the one that drew the most attention in for being part of the formation of vesicular body and be related to the processes of antigen presentation. The synthetic peptide MEG-12 has a peculiar characteristic of an amphipathic helix predicted by Jpred3 program, and hemolytic character. This action was best observed by scanning electron microscopy (SEM), to be verifies in a clear disruption of the membrane to the breakup. The peptide is secreted into the esophagus may region associated with the digestion of erythrocytes made by the parasite. Therefore, these two proteins are shown to be important in the host-parasite relationship and possible targets for drugs or creation of more efficient vaccines.